The management of patients who self-harm in adult inpatient mental health settings: A policy analysis of English NHS mental health trusts - Hannah Sharp; Judith Johnson; Cathy Brennan; John Baker (PLoS ONE, 2025)
The management of self-harm is a critical focus for staff in inpatient mental health settings. This study aimed to better understand how staff are guided through policies to manage self-harm via the following objectives: 1) to assess the alignment of policies from English NHS Mental Health trusts with national guidelines, 2) identify which aspects of the national guidelines are most and least frequently reflected in these policies, and 3) determine whether trusts with dedicated self-harm policies better reflect national guidelines. We conducted a content analysis of self-harm-related policies across 50 English NHS mental health trusts against a framework of 20 standards created from National Institute for Health and Care Excellence self-harm guidelines. Our analysis revealed a significant difference (U = 36.50, p = .002) in the number of standards met by trusts with a specific self-harm policy (M = 11.44, SD = 3.00) compared to those without (M = 7.26, SD = 3.00), with the number of standards met ranging from zero to 15. Notably, trusts failed to meet the majority of standards (M = 11.69, SD = 3.30). The findings of this study highlight several new insights into NHS trust policy on self-harm: 1) trusts exhibit variability in how they organise information across their policies, 2) dedicated self-harm policies may support trusts to better meet guidance but risk complicating guidance for staff, 3) policy content varies across trusts, 4) the importance of patient voice is acknowledged but the facilitators of good participation are poorly supported in the same policies, 5) trusts rarely define self-harm and some trusts use definitions which do not reflect guidelines, and 6) harm-reduction remains underrepresented in policies, reflecting ongoing contention surrounding its implementation. Further research is needed to understand the role that policy and guidelines play in guiding staff practices when managing self-harm.